Meeting Farmers Where They Are – Rural Clinicians' Views on Farmers' Mental Health. Issue 1 (2nd January 2020) - Cole, Donald C; Bondy, Madeleine C
ABSTRACT: Objective : To explore rural clinicians' understanding of farmers' mental health and well-being, current health services, and potential responses. Methods : Qualitative design, with semi-structured, taped interviews of five family physicians and four mental health nurses-counselors practicing in rural Grey–Bruce counties, Ontario. Transcripts analyzed with N-Vivo through iterative coding of emergent themes and mapping of relationships among themes. Results : Participating rural clinicians all expressed admiration for farmers. They shared insights around three main themes: 1) farming as a unique subculture; 2) farming involved both benefits and challenges for health; and 3) farmers rarely seek care. Clinicians need to take advantage of contact opportunities to ask about mental health. Several suggested ways to meet farmers where they are, e.g., through better funding for house-farm calls and community events. Conclusion : Clinician responses to farmers' mental health challenges include recognizing farmers' distinct context. Complementary health promotion in conjunction with farm organizations is needed to reach farmers.